INNOVATIVE PEDAGOGICAL METHODOLOGIES FOR INTEGRATING CRITICAL THINKING INTO ENGLISH LANGUAGE TEACHING - Isroilova , Mohinur (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This thesis explores innovative pedagogical methodologies that can effectively embed critical thinking skills within English language classrooms. Drawing upon constructivist learning theories, task-based instruction, project-based learning, problem-solving approaches, and multimodal teaching strategies, the study highlights how English language teaching can evolve beyond rote learning toward cultivating independent, reflective, and creative learners. By examining both theoretical foundations and practical applications, the thesis underscores the potential for innovative methods to transform English language classrooms into spaces where critical thinking and linguistic competence develop simultaneously.